If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -9 = 7y + -1 Reorder the terms: -9 + 6y = 7y + -1 Reorder the terms: -9 + 6y = -1 + 7y Solving -9 + 6y = -1 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -9 + 6y + -7y = -1 + 7y + -7y Combine like terms: 6y + -7y = -1y -9 + -1y = -1 + 7y + -7y Combine like terms: 7y + -7y = 0 -9 + -1y = -1 + 0 -9 + -1y = -1 Add '9' to each side of the equation. -9 + 9 + -1y = -1 + 9 Combine like terms: -9 + 9 = 0 0 + -1y = -1 + 9 -1y = -1 + 9 Combine like terms: -1 + 9 = 8 -1y = 8 Divide each side by '-1'. y = -8 Simplifying y = -8
| 3-x=2.25 | | 6x^2+24x+30=0 | | 2(3X+5)=5X+5 | | 7z+11=0 | | 132=2l+3w | | 10=3z-8 | | 3x-(6-x)=18 | | 5d-2=2d+6 | | 36x=36+121+1 | | t^2-5t+2fort=-4 | | -x=-0.12 | | f(0)=-2x | | 9+11x=107+x | | 4(3x+2)=11+2 | | 4g+1=5g-1-g | | 8x+1=6x+37 | | 24s-53=49-s | | -2t+5t=-8+4 | | 1.25x+4.25=-7 | | -1.2(z-13)=-2.1(z-16) | | 60(x+24)=80x | | 4(3)-4(-7)= | | -u+24=-5u | | 2(3)-4(-7)= | | r^2-5t-24=0 | | x+1-2-(-x+3)=6-(-1+1) | | x^2-x-6=x^2+x-6 | | 8(4x+6)=4(2+10x) | | 7.5a+5=2.5a+13 | | 68-42b=56b-3 | | 2(x^2+x)+3(x^2y+xy)= | | 2w+2(w+6)-12=4w |